New fermented plant-based ingredients in sourdough breads enhanced nutritional value and impacted on gut microbiota - Federica Mastrolonardo; Alice Costantini; Andrea Polo; Michela Verni; Wilson José Fernandes Lemos Junior; Ali Zein Alabiden Tlais; Olga Nikoloudaki; Lena Birgitta Marie Granehäll; Marco Gobbetti; Erica Pontonio; Raffaella Di Cagno (Future Foods)
Two new recipes of baker's yeast bread fortified with fermented apple by-products and avocado or walnut were designed resulting in enhanced profiles of total free amino acids, in vitro protein digestibility (IVPD) and predicted glycemic index (pGI). Concurrently, pools of lactic acid bacteria and yeast were screened to select the most promising starters for sourdough preparation. The type II sourdough with Lactiplantibacillus plantarum CR1, Furfurilactobacillus rossiae CR5 and Saccharomyces cerevisiae E10 had the highest acidification and total free amino acids value, while resulting in bread with the highest IVPD and the lowest pGI.Sourdough breads were manufactured with the new recipes. They had improved protein digestibility and starch hydrolysis, and enhanced content of dietary fiber, phenolics and unsaturated free fatty acids. The impact of new fortified sourdough breads on colon microbial ecosystems was investigated by the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®). The intake promoted the short-chain fatty acids synthesis and expanded several bacterial taxa with potential to exert beneficial activities. The synergic combination of sourdough fermentation and fortification with fermented plant-based matrices (including by-products) was a suitable strategy to promote better nutritional and digestibility properties in breads, and to promisingly address the modulation of gut microbiota.